The Role of Probation Officers in Implementing Guidance for Adult Clients Who Receive Reintegration at Class I Medan Correctional Center - Lindawati Br Surbakti; Suci Ramadani; Rahmayanti Rahmayanti (International Journal of Law, Crime and Justice, 2025)
Guidance is one of the duties of the Community Guidance Officer which aims to make correctional clients, both adult clients and child clients, become better people, can be accepted in the midst of family and society. Since the enactment of Law Number 22 of 2022 concerning Corrections, the role of Community Guidance Officers is very important because Community Guidance Officers are tasked with accompanying clients while they are in and outside the criminal justice process to prepare clients for the social reintegration process. The research method used in this study is empirical juridical. The data used in this study uses a descriptive analytical approach, namely research that describes and analyzes data obtained from interviews, documents, and field notes. Guidance carried out by Community Counselors for adult clients begins at the pre-adjudication, adjudication, post-adjudication and follow-up guidance stages with the understanding that after the reintegration program has been successfully proposed, the client will receive a Decree (SK) and will be handed over by officers from the Correctional Institution or State Detention Center to the Correctional Center, then that is the beginning of the guidance stages carried out by Community Counselors. Community Guidance at the Medan Class I Correctional Center also faces obstacles in implementing guidance for adult clients, but several efforts have been made to reduce obstacles with the aim of preventing adult clients from repeating criminal acts that cause client reintegration guidance to be terminated and must be revoked.